2022
DOI: 10.1002/hed.27179
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic pituitary surgery: National database review

Abstract: Background Pituitary tumors surgery is increasingly performed via endoscopic transsphenoidal approach (TSP). This study describes outcomes of TSP surgery in the United States. Methods A retrospective cross‐sectional analysis of adult patients with pituitary adenoma was performed using the Nationwide Readmissions Database, 2010–2015. Results A total of 5891 patients were identified. The average age was 51.29 ± 0.29 years. The risk of postoperative epistaxis, diabetes insipidus, cerebrospinal fluid (CSF) leak, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Our rates of development of DI in 21.4% of patients and SIADH in 7.4% of patients are comparable to other published rates of 10 to 60% and 4 to 23%, respectively. [8][9][10][11][12][13] Our mean onset of DI at 2.6 days was comparable to previous reports of onset of less than 5 days after TSH, 9,11,18 whereas SIADH onset at 4.7 days at TSH was earlier compared with a previous report of onset at 7 days. 11 We found that older age was a negatively associated factor with development of DI, similarly to previous studies that identified younger age (e.g., less than 50 years old) as a risk factor for development of DI.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our rates of development of DI in 21.4% of patients and SIADH in 7.4% of patients are comparable to other published rates of 10 to 60% and 4 to 23%, respectively. [8][9][10][11][12][13] Our mean onset of DI at 2.6 days was comparable to previous reports of onset of less than 5 days after TSH, 9,11,18 whereas SIADH onset at 4.7 days at TSH was earlier compared with a previous report of onset at 7 days. 11 We found that older age was a negatively associated factor with development of DI, similarly to previous studies that identified younger age (e.g., less than 50 years old) as a risk factor for development of DI.…”
Section: Discussionsupporting
confidence: 84%
“…11 These complications directly impact postoperative course and patient care, with previous studies documenting the rate of transient DI following transsphenoidal adenoma resection varying from 10 to 60%. [8][9][10][11][12][13] Although DI peaks on average at postoperative day 5 and dissipates by day 11, rates of persistent DI lasting longer than 3 months have been observed to range from 2 to 10.1%. 8,10,11 SIADH occurs at slightly less common rates of 4 to 23% of pituitary adenoma resection patients and occurs around postoperative day 7.…”
Section: Introductionmentioning
confidence: 99%
“…15 A 2010 to 2015 study of the Nationwide Readmissions Database reported a 0.7% risk of epistaxis after TSS for pituitary adenoma, while a 2018 single-institution study reported an epistaxis rate of 1.1%. 16,17 This single-institution study also reported a 1.1% risk of postoperative hematoma after TSS for pituitary adenoma. 17 A feared complication is suprasellar hematoma, which can affect vision.…”
Section: Discussionmentioning
confidence: 57%
“…The rate of CSF leakage in an American national database including 5891 patients was 8.35%. 38 Duz et al reported that CSF leakage occurred in 11% of his endoscopic group. 42 A paper published in 2020 with 270 patients, including pituitary adenomas among other pathologies, found a 9% incidence of CSF leak.…”
Section: Discussionmentioning
confidence: 95%